TINJAUAN HUKUM ATAS DIBATALKANNYA AKTA JUAL BELI OLEH PENGADILAN NEGERI TERHADAP BPHTB YANG TELAH DIBAYARKAN - Miftahur Rachman (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2020)
This study, entitled this study, aims to determine the legal consequences of the cancellation of the deed of sale and purchase of land rights that were canceled by a court decision and the consequences for the acquisition of land and building rights fees (BPHTB) that had been paid. This research is normative juridical research. Based on the results of the existing discussion, the results of this study are: First, the result of the cancellation of the sale and purchase deed which was canceled by the court decision resulted in the withdrawal of the BPHTB having no legal basis again, so that BPHTB restitution should be carried out by the taxpayer or the party concerned. Second, the legal protection given to taxpayers or parties for restitution of BPHTB is by submitting objections or requests to the local regional government which is given the authority to the BKAD of each region